Goethe dan Aspek Multikultural Sastra Dunia - Lilawati Kurnia (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2006)
When we use the term 'World Literature', what comes into our minds is the meaning of the two words, what is the mean by World?Literature? We can browse through the internet and try to find the meaning of this phrase in the cyber world, but can all definitions and lists of works from the many writers in the sites actually be acknowledged as World Literature? Moreover, if we try  to explore the two words, does 'literature' only refer to literary works or all kinds of literature including books? The next word is 'world' of course has its own problem because we do not actually know whether it means the whole world in which every single literary work on earth is considered as world literature or it only refers to certain parts of the world like Europe and America.       The phare Weliliteratur was first articulated by a German writer, Wieland, in the context of world culture that privileges literary works in order to bring people to the world. It was quite different when Goethe used this phrase in his letter to Karl Streckfub, a translator of Italian classical works on 27 January1927, and Goethe used the word Welt in acontext of literature beyond the national context, literature outside German across national boundaries. Goethe articulated it by saying:       "I am more convinced, "Goehte remarked, " that poetry is the universal possession of mankind, revealing itself everywhere and at all times in hundreds and hundreds of men... I therefore like to look about me in foreign nations, and advise everyone to do the same. National literature is now a rather unmeaning term; the epoch of world literature is at hand, and everyone must strive to hasten its approach."       The term used by Goethe gives out a modern sense which suits the globalize era where we live now. In this case, Goethe seemed to be ahead of his time in making a literary contribution.